Enhancement Of Manchester Encoding Technique By Combining IT With A Hash Function - Hamarsheh, Mu'taz M. N. (2008)
This study proposes a combination of Manchester encoding technique and SHA-1 hash function, to provide a secure data transmission over a client/server environment by sending the message digest along with the message, and compare it with a new generated message digest on the server. Hash function improves integrity to the transmitted message. Manchester encoding technique is chosen to encode the transmitted message because it encodes both data and clocks into a form of synchronous bit stream. The modification of the message during the transmission, results in changing the message digest. This shows that including the SHA-1 hash function with Manchester encoding technique the integrity of the data can be accomplished.